Evaluation of substrates for seedlings establishment in laboratory of Puya raimondii Harms (Bromeliaceae) - Vadillo, Giovana (2006)
Puya raimondii Harms (Bromeliaceae) is a monocarpic plant, that can produce about 6 to 12 million seeds, nevertheless is very rare to find seedlings in their natural habitat, indicating difficulties for its establishment. In this work, the conditions for establishment of P. raimondii under laboratory conditions were determined carrying out experiments to determine the better substrate. It was compared the survival and vigour of P. raimondii seedling that were transplanted in peat, moss, peat-soil and moss-soil substrates. The peat substrate showed high survival and was better for establishment of seedlings because it maintains steady and suitable humidity and pH conditions, this allowed that seedlings presents a good vigour. Substrates with very little (case peat-earth) or too much (case moss) humidity retention had a negative effect over vigour and development.